Processo comunicativo do agente comunitário de saúde durante a abordagem com gestantes e puérperas vivendo com HIV - Oliveira, Jocélia Maria de (2013)
The performance space of the community health worker has as its main focus the monitoring of women in pregnancy and childbirth, in that scenario develops his communicative action, surrounded by relations that demarcate the need for coordination with patient, community and other professionals who make up the staff of the Family Health Strategy. Increased detection of HIV in the presence of pregnancy has shown the need for further monitoring to ensure adherence to treatment and care will promote this pregnant. Given the complexity of this relationship, we aimed to understand the communication process established during the Community Health Worker approach with pregnant and postpartum women seropositive for HIV, identify the strategies that you use this process, as well as their strengths and difficulties. Qualitative study, developed in light of symbolic interactionism, interviewing eight Community Health Worker accompanying pregnant and postpartum women seropositive for HIV from January 2007 to July 2012 in the city of Canindé-CE. The empirical corpus was categorized into five main categories: 1. Identifying pregnant / postpartum women with HIV in the community; 2. Meaning of HIV to ACS; 3. Monitoring conducted by Community Health Worker; 4. Unveiling the communication process during the ACS approach with pregnant and postpartum women seropositive for HIV; 5. Connections with the "life-world". The results were analyzed according to the technique of discourse analysis, with reflections grounded in the theoretical framework of Habermas, Morin and literature. We identify the pregnant woman reveals his HIV status to Community Health Worker due to the bond built and ease of access to health services. Moreover, the host of humanized Community Health Worker relates to the feeling of sadness attributed to the disease. Despite seek conceptualize ethics as secrecy, there is a conflict between communication and ethics in the selfunderstanding of this concept in the disclosure of information in the health team. Develop your communication with women when describing their orientations in a dynamic and cyclic, based on a strategic action by a levy disguised, inducing pregnant / postpartum women to accept his conviction as valid. Despite being a strategy that avoids the communicative action proposed by Jurgen Habermas, the community health worker are happy to have the confidence of women and because they represent a reference point for the community but the difficulties as work overload, lack of training permanent uncertainty in its role and problems of socio-economic order experienced by pregnant women.